Validation of analytical models for the design of basal reinforced piled embankments - van Eekelen, S.J.M.; Bezuijen, A.; van Tol, A.F. (Geotextiles and geomembranes, 2015)
Van Eekelen et al. (2012a,b, 2013) have introduced an analytical model for the design of the geosynthetic reinforcement (GR) in a piled embankment. This paper further validates this model with measurements from seven full-scale tests and four series of scaled model experiments. Most of these measurements have been reported earlier in the literature. The new model describes arching with the “Concentric Arching model” (CA model). This model is an extension of the single arch model of Hewlett and Randolph (1988) and the multi-scale model of Zaeske (2001), which is also described in Kempfert et al. (2004). For load-deflection behaviour, Van Eekelen et al. (2012a,b, 2013) proposed the use of a net load distribution that is inverse triangular instead of uniform or triangular. These authors also proposed the inclusion of all the subsoil support beneath the GR in the calculations. On the basis of comparisons between the measurements and calculations, it is concluded that the CA model matches the measurements better than the models of Zaeske or Hewlett and Randolph. Where there is no subsoil support, or almost no subsoil support, the inverse triangular load distribution on the GR strips between adjacent piles gives the best match with the measurements. Cases with subsoil support generally lead to less GR strain. In the cases with significant subsoil support, the load distribution is approximately uniform. In the cases with limited subsoil support, it should be determined which load distribution gives the minimum GR strain to find the best match with the measurements.